2015
DOI: 10.1155/2015/349721
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive and Angiotensin-Converting Enzyme Inhibitory Activities ofEisenia fetidaExtract in Spontaneously Hypertensive Rats

Abstract: Objectives. This study aimed to investigate the antihypertensive effects of an Eisenia fetida extract (EFE) and its possible mechanisms in spontaneously hypertensive rats (SHR rats). Methods. Sixteen-week-old SHR rats and Wistar-Kyoto rats (WKY rats) were used in this study. Rats were, respectively, given EFE (EFE group), captopril (captopril group), or phosphate-buffered saline (PBS) (normal control group and SHR group) for 4 weeks. ACE inhibitory activity of EFE in vitro was determined. The systolic blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
1
1
1
Order By: Relevance
“…In our current study, we found there was a negative correlation between the plasma aldosterone concentration and the number of RGCs in the central and peripheral retina. Although a previous study reported finding the plasma aldosterone concentration in normal rats to be approximately 180 pg/ml, 23 our current study found that the plasma aldosterone concentration in rats treated with vehicle was 212 ± 17 pg/ml. This difference suggests that the normal value of aldosterone might depend on the species examined.…”
Section: Discussioncontrasting
confidence: 89%
“…In our current study, we found there was a negative correlation between the plasma aldosterone concentration and the number of RGCs in the central and peripheral retina. Although a previous study reported finding the plasma aldosterone concentration in normal rats to be approximately 180 pg/ml, 23 our current study found that the plasma aldosterone concentration in rats treated with vehicle was 212 ± 17 pg/ml. This difference suggests that the normal value of aldosterone might depend on the species examined.…”
Section: Discussioncontrasting
confidence: 89%
“…In agreement with our observations, the antihypertensive activity and AT1 receptor blocking activity of benzimidazoles like candesartan ( Nagai et al, 2004 ) and substituted benzimidazoles like 5-nitro benzimidazoles ( Shah et al, 2008 ), and 1, 4 or 1, 5 di-substituted benzimidazoles ( Zhu et al, 2014 ) were also reported. SHR are known to have a very high level of angiotensin II expression and downstream AT1 receptor activation for the induction of high blood pressure ( Mao and Li, 2015 ) and hence AT1 receptor blockers were found to be the most frequently reported antihypertensive agent in these models ( Choisy et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sebanyak 1 mL lapisan etil asetat diambil lalu diuapkan pada tangas air. Hasilnya dilarutkan dengan 3 mL aquadeion lalu diukur absorbansinya dengan spektrofotometri uv-sinar tampak pada panjang gelombang 228 nm (Muthia et al 2017, Mao and Li 2015, Jamhari et al 2013, Prasanna et al 2012. Persen inhibisi dihitung melalui persamaan:…”
Section: Pengujian Efek Inhibisi Angiotensin Converting Enzyme (Ace) ...unclassified